Pendulums and Prosody in the Long Eighteenth Century. (27th February 2017) - Tomalin, Marcus
Abstract: During the long eighteenth century, metaphors and analogies associated with clockwork mechanisms were frequently used to critique the perceived constraints of Augustan prosody. Despite this, a new generation of theorists, who rejected established prosodic conventions and proposed less restrictive metrical practices, frequently deployed references to pendulums positively when emphasizing the advantages of greater prosodic flexibility. Consequently, the image of a swinging bob became a deeply conflicted one in discussions of versification during this period. Accruing diametrically opposed associations, the analogy could denote oppressive regularity but also liberating variety. Drawing extensively on existing studies of prosodic theory and practice, this article explores these puzzling tendencies, arguing that pendulums were able to serve these antithetical rhetorical purposes because they were allied to organic as well as mechanical phenomena. Therefore they could function in an intermediary capacity, synchronizing the isochronicities of literature with those of the natural world. This development sheds a revealing light on how changing perceptions of the relationship between mechanism and organicism came to characterize the different theories of prosody that emerged as the long eighteenth century advanced.